Feeding habit and diet composition of three fish species inhabiting Sor River, Baro-Akobo Basin of Ethiopia, East Africa - Tujuba Ayele Tesso; Limatu Kebede Nurgi (PLoS ONE, 2025)
The purpose of this study was to investigate feeding habit and diet composition of three fish species (Oreochromis niloticus, Labeo forskalii and Labeobarbus intermedius ) inhabiting Sor River, Baro-Akobo basin of Ethiopia. Stomach contents of these fish species were examined. A total of 73 fish gut samples were collected from fishermen on site from February to March 2022. The diet composition of each species was analysed and expressed as percentage of frequency of occurrence (% F), numerical occurrence and gravimetric composition (% G). The major food items in the stomach of each species were determined using percentage index of relative importance (% IRI). The study showed that O. niloticus from Sor River feeds on phytoplankton, macrophytes and detritus as major prey. The stomach of L. forskalii was found to have Phytoplankton, macrophytes, insects, fish larvae, detritus and others. The gut content analysis of L. intermedius revealed phytoplankton and detritus found to be the dominant food constituents with % IRI 23.72% and 28.04% respectively. Fish larvae and flatworms are important diet constituents. The diet breadth index which measures the diversity of prey items consumed by each fish species was 0.43 for O. niloticus, 0.61 for L. intermedius and 0.64 for L. forskalii, respectively. According to their diet breadth and overlap indices, the three fish species had an omnivorous feeding habit which is useful to enhance fisheries and aquaculture development in the study area.